Economic freedom in retrospect - Prados de la Escosura, Leandro (European Historical Economics Society, 2023)
This paper analyses economic freedom for a sample of 21 OECD countries over the past 170 years on the basis of a new thoroughly revised Historical Index of Economic Liberty (HIEL). Long-term gains in economic freedom reached two-thirds of its potential maximum. The expansion of economic freedom was abruptly interrupted by the world wars and resumed after 1950, to peak in 2000 and stagnate thereafter. International openness has been its main contributing dimension, especially after 1950. Stability in the country ranking coexisted with a narrowing of the distance between countries' levels of economic freedom.
10419/298534
Keywords: Graue Literatur; Economic Freedom; Property Rights; Price Stability; Openness; Regulation; OECD